2002
DOI: 10.1016/s0008-6363(01)00437-0
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of beta-adrenergic inotropic response by pyruvate in failing human myocardium

Abstract: A combination of pyruvate and beta-adrenergic stimulation may be of therapeutic value in acute heart failure by reducing the concentrations of potential deleterious catecholamines that are currently necessary to maintain adequate tissue perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Likewise, an increase in stimulation frequency increases the developed calcium transient and accelerates both calcium and force decline [27], [36]. In accordance with previous studies, we too observed that upon addition of pyruvate the calcium transient increases, but the decline of force does not increase, it actually is significantly slowed [3], [7], [8]. We demonstrated here that the increased SR calcium handling is not the primary underlying molecular mechanism for pyruvate’s inotropic effect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, an increase in stimulation frequency increases the developed calcium transient and accelerates both calcium and force decline [27], [36]. In accordance with previous studies, we too observed that upon addition of pyruvate the calcium transient increases, but the decline of force does not increase, it actually is significantly slowed [3], [7], [8]. We demonstrated here that the increased SR calcium handling is not the primary underlying molecular mechanism for pyruvate’s inotropic effect.…”
Section: Discussionsupporting
confidence: 92%
“…Pyruvate’s effects in augmentingthe contractile strength of the heart have been shown to be consistent throughout several species including rat, rabbit, swine, and humans [4], [5], [6], [7]. It potentiates the effect of β-adrenergic drugs [8] and it has been infused intracoronary in humans experimentally to increase inotropic support [4], [9].…”
Section: Introductionmentioning
confidence: 98%
“…Application of pyruvate in this model improved both energetic and hemodynamic parameters [4]. Accordingly, application of pyruvate to human heart failure patients in vivo increased LV systolic and diastolic function [87,88], which was related to an increase of SR Ca 2+ load and thus, cytosolic Ca 2+ transient amplitude in vitro [82,89].…”
Section: Pathophysiological Aspects Defects In Ec Coupling In Chronicmentioning
confidence: 84%
“…Some of these concerns in regards to utilizing human samples have been discussed by others as well (Jweied, et al, 2007; Marston & de Tombe, 2008). Still, despite these difficulties, in vitro assessment of contraction in human cardiac tissue can be an important tool to study drugs or physiological processes (Hermann, et al, 2002; Janssen, et al, 1999; Janssen, et al, 2000; Pieske, et al, 1995; Rossman, et al, 2004). …”
Section: Verification Using Human Tissuementioning
confidence: 99%